A comparative study of problem-solving in English-to-Chinese sight translation - Cheah, Fong Yee (Nanyang Technological University, 2020)
Sight translation has developed into an increasingly important form of practice over the past decades. Some scholars consider it as a hybrid form of language mediation which shares visual input with written translation and oral output with interpreting. Although sight translation is widely taught as a preparatory course in interpreting programme, there is little attention devoted to the research of problem-solving in sight translation process, particularly with English and Chinese being the source language and target language. This paper sets out to examine the performances of ten trained translators and ten untrained translators in an English-to-Chinese sight translation task, with the aim to identify the translation challenges and strategies in sight translation. Firstly, long pauses in the oral outputs were counted and measured to investigate processing difficulties during the translation process. Secondly, retrospective think aloud protocols were used as research methods to elicit self-reported translation problems and strategies. The product-based and process-based analysis revealed that the majority of the translation problems emerged during the comprehension stage, where the presence of source text and the complexities of written language created the greatest obstacle for both the trained and the untrained. It was found that the untrained encountered with more problems in source language to target language transfer stage. Whereas the trained translators were more competent in encoding message into target language as they were able to apply logical analysis to predict subsequent translating segments, thus facilitating the activity of reading ahead. These findings have pedagogical value that the use of anticipation strategy by the trained translators can serve as an important skill in ST training.